PERILAKU SEKSUAL REMAJA DALAM BERPACARAN DITINJAU DARI HARGA DIRI BERDASARKAN JENIS KELAMIN - Fridya Mayasari; M Noor Rochman Hadjam (Faculty of Psychology, Universitas Gadjah Mada, 2000)
The purpose of this research is to find the correlation between self esteem and adolescent’s sexual behavior on dating. Self esteem has been measured on specific and connected with sexuality context. Frequency of changing partners has become covariable. Senior high school students who are on dating became the sample of this research, consist of 85 boys and 87 girls. The result of this research indicate that the correlation between adolescent’s sexual behavior on dating with their self esteem wasn’t significant among boys and was among the girls. Keywords: Adolescent’s sexual behaviour.